All-fiber femtosecond Cherenkov radiation source - Liu, Xiaomin (2012)
An all-fiber femtosecond source of spectrally isolated Cherenkov radiation is reported, to the best of our knowledge, for the first time. Using a monolithic, self-starting femtosecond Yb-doped fiber laser as the pump source and the combination of photonic crystal fibers as the wave-conversion medium, we demonstrate stable and tunable Cherenkov radiation at visible wavelengths 580–630 nm, with pulse duration of sub-160-fs, and the 3 dB spectral bandwidth not exceeding 36 nm. Such an all-fiber Cherenkov radiation source is promising for practical applications in biophotonics such as bioimaging and microscopy.